Analisis Kualitas Layanan E-Government pada Website Pemerintah Kabupaten Malang dengan Dimensi E-Govqual dan Importance-Performance Analysis (IPA) - Dzat Dini Roso; Aditya Rachmadi; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Malang Regency is one of the districts that continuously develops e-government to serve community needs. As long as the system is running there has been no evaluation and assesment to service quality based on the end-user's perception. This study aims to assess the quality of website services of Malang Regency Government based on user perceptions, knowing what attributes are priority improvements and providing recommendations for improvements. This research uses e-govqual which is the right dimension to assess government services that combined with Importance-Performance Analysis (IPA). This reseacrh uses 4 variables from e-govqual, namely efficiency, trust, reliability and citizen support consist of 21 indicators. Respondents are involved in this research were 111 people. Data obtained by distributing questionnaires that had previously been tested with validity and reliability tests. The overall level of suitability is 83.65%, while the gap value obtained is -0.521. Variables that need improvement are citizen support variables and several indicators for reliability and efficiency. The research results show that overall the quality of Malang Regency website has not fulfilled the expectations of users. Recommendations for improvements provided include periodic maintenance, updating software and hardware to meet service capacity, adding customization features, adding chat features, providing training to officers and adding Frequently Answer-Question (FAQ) pages.